Housing as a Social Determinant of Health: Exploring the Relationship between Rent Burden and Risk Behaviors for Single Room Occupancy Building Residents. Issue 5 (28th July 2016) - Bowen, Elizabeth A.; Mitchell, Christopher G.
Abstract : A growing body of health determinants research recognizes that housing and health are intimately linked. This study explores the relationship between rent burden (the ratio of rent to income) and health risk behaviors among a sample of single room occupancy (SRO) building residents. Cross-sectional data were gathered from a sample of 162 residents living in privately owned, for-profit SROs in Chicago. Findings indicated that participants who had full rental subsidies and thus were designated in a no-rent-burden category were more likely to engage in risk behaviors including illicit drug use, having multiple sexual partners, and having sex without a condom, in comparison to participants with moderate or high-rent burdens. These findings suggest that interventions to increase housing stability and affordability and bolster reliable income sources (in addition to rental subsidies) may be key in reducing risk behaviors and improving health for vulnerably housed populations such as SRO residents.